PENGARUH LATIHAN AEROBIK INTENSITAS SEDANG TERHADAP KEBUGARAN JANTUNG PARU PADA PASIEN SKOLIOSIS DI RSUD ULIN BANJARMASIN - Ramadan, Yoga Aditya Noor; Hayati, Azka; Asnawati, Asnawati; Siddik, Muhammad; Marisa, Dona (Universitas Lambung Mangkurat, 2024)
Abstract: Patients with scoliosis experience changes in the shape of the spine and ribs that can affect cardiorespiratory fitness (VO2 max). Cardiorespiratory fitness is related to a person's ability to perform moderate to heavy intensity exercise continuously for a long time. One of the exercises to increase VO2 max is aerobic exercise. The purpose of this study was to determine the effect of moderate intensity aerobic exercise on cardiorespiratory fitness in scoliosis patients. This research is quasi-experimental with a one group pretest and posttest research design with no control group. The research subjects were scoliosis patients who met the inclusion criteria totaling 4 people who were taken at the medical rehabilitation section of Ulin Banjarmasin Hospital in the October-November 2023 period. Subjects were treated with moderate intensity aerobic exercise by walking 20 minutes/exercise, 3 times a week, for 4 weeks; then cardiorespiratory fitness test was applied using the 6-minute walk test method. The mean VO2 max value before aerobic exercise was 16.84±1.887 and after exercise was 23.60±5.168. The results of data analysis using paired t test from the mean VO2 max before and after training obtained p=0.047. It can be concluded that there is a significant effect of moderate intensity aerobic exercise on cardiorespiratory fitness in scoliosis patients at Ulin Hospital Banjarmasin. Keywords: scoliosis, cardiopulmonary fitness, VO2 max, aerobic exercise. Abstrak: Penderita skoliosis mengalami perubahan bentuk tulang belakang dan tulang rusuk yang dapat mempengaruhi fungsi kebugaran jantung paru (VO2 maks). Kebugaran jantung paru berhubungan dengan kemampuan seseorang untuk melakukan latihan dengan intensitas sedang hingga berat secara terus-menerus dalam waktu yang lama. Salah satu latihan untuk meningkatkan VO2 maks adalah latihan aerobik. Tujuan dari penelitian ini adalah untuk mengatahui pengaruh dari latihan aerobik intensitas sedang terhadap kebugaran jantung paru pada pasien skoliosis. Penelitian ini bersifat quasi eksperimental dengan desain penelitian one group pretest and posttest with no control group. Subjek penelitian merupakan penderita skoliosis yang memenuhi kriteria inklusi yang berjumlah 4 orang yang diambil di bagian rehabilitasi medik RSUD Ulin Banjarmasin periode Oktober-November 2023. Subjek diberi perlakuan latihan aerobik intrensitas sedang dengan berjalan kaki 20 menit/latihan, 3 kali seminggu, selama 4 minggu; kemudian dilakukan uji kebugaran jantung paru menggunakan metode uji jalan 6 menit. Didapatkan rerata nilai VO2 maks sebelum latihan aerobik 16,84±1,887 dan setelah latihan 23,60±5,168. Hasil analisis data menggunakan uji t berpasangan dari rerata VO2 maks sebelum dan setelah latihan didapatkan nilai p=0,047. Dapat disimpulkan bahwa terdapat pengaruh yang signifikan latihan aerobik intensitas sedang terhadap kebugaran jantung paru pada pasien skoliosis di RSUD Ulin Banjarmasin. Kata-kata kunci: skoliosis, kebugaran jantung paru, VO2 maks, latihan aerobik.